Purinergic signaling: Diverse effects and therapeutic potential in cancer - Kaur, Jasmeet; Dora, Sanchit (Frontiers in Oncology, 2023)
Regardless of improved biological insights and therapeutic advances, cancer is consuming multiple lives worldwide. Cancer is a complex disease with diverse cellular, metabolic, and physiological parameters as its hallmarks. This instigates a need to uncover the latest therapeutic targets to advance the treatment of cancer patients. Purines are building blocks of nucleic acids but also function as metabolic intermediates and messengers, as part of a signaling pathway known as purinergic signaling. Purinergic signaling comprises primarily adenosine triphosphate (ATP) and adenosine (ADO), their analogous membrane receptors, and a set of ectonucleotidases, and has both short- and long-term (trophic) effects. Cells release ATP and ADO to modulate cellular function in an autocrine or paracrine manner by activating membrane-localized purinergic receptors (purinoceptors, P1 and P2). P1 receptors are selective for ADO and have four recognized subtypes—A1, A2A, A2B, and A3. Purines and pyrimidines activate P2 receptors, and the P2X subtype is ligand-gated ion channel receptors. P2X has seven subtypes (P2X1–7) and forms homo- and heterotrimers. The P2Y subtype is a G protein-coupled receptor with eight subtypes (P2Y1/2/4/6/11/12/13/14). ATP, its derivatives, and purinoceptors are widely distributed in all cell types for cellular communication, and any imbalance compromises the homeostasis of the cell. Neurotransmission, neuromodulation, and secretion employ fast purinergic signaling, while trophic purinergic signaling regulates cell metabolism, proliferation, differentiation, survival, migration, invasion, and immune response during tumor progression. Thus, purinergic signaling is a prospective therapeutic target in cancer and therapy resistance.